2019
DOI: 10.1093/cid/ciy1116
|View full text |Cite|
|
Sign up to set email alerts
|

Salmonella Typhi From Blood Cultures in the Democratic Republic of the Congo: A 10-Year Surveillance

Abstract: Background This study gives an overview of a decade (2007–2017) of hospital-based Salmonella Typhi bloodstream infection (BSI) surveillance in the Democratic Republic of the Congo (DRC), at 4 main sampling sites. Methods Blood cultures were sampled in hospital-admitted patients with suspected BSI, according to standardized clinical indications. The results of the surveillance period 2015–2017 were compiled with those of previous surveillance p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Lastly, the date of onset of symptoms was not registered, nor was the occurrence of gastrointestinal symptoms. As to its strengths, blood cultures were systematically sampled based on harmonized indications and the hospital staff got the trust of the patient's families facilitating enrollment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, the date of onset of symptoms was not registered, nor was the occurrence of gastrointestinal symptoms. As to its strengths, blood cultures were systematically sampled based on harmonized indications and the hospital staff got the trust of the patient's families facilitating enrollment [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study took place from November 2013 to April 2017 at the hospital of Saint-Luc in Kisantu (HSLK), Kongo-Central province, Democratic Republic of the Congo (DR Congo). HSLK is the major sampling site of the microbiological surveillance network organized by the Institut National de Recherche Biomédicale (INRB), Kinshasa, DR Congo, and the Institute of Tropical Medicine, Antwerp, Belgium [4,14]. Over a 10-year period (2007-2017), NTS ranked first as a cause of BSI in children accounting for 63.8% of culture-confirmed BSI [14,15].…”
Section: Study Site and Study Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this spectrum can vary considerably in different sites and settings. Surveillance can therefore determine the occurrence and proportions of geographically confined pathogens such as Burkholderia pseudomallei (melioidosis, South-East Asia) (53), Streptococcus suis (zoonotic meningitis and sepsis, Asia) (55) and Salmonella species (both typhoidal and non-typhoidal) (54, 63, 64). Consistent blood culture surveillance as part of capacity building projects also allows for early alerts for hospital and community outbreaks (Box 3).…”
Section: The Clinical Bacteriology Laboratory Allows For Antimicrobiamentioning
confidence: 99%
“…The most common Gram-positive bacteria were coagulase-negative Staphylococcus (CNS) and Staphylococcus aureus (Fig 2) Our study showed that S. typhi was also a main BSI-associated pathogen in Hubei Province from 1998-2003. Typhoid fever is a poverty-related disease, mainly occurring in Africa and Asia, with a low incidence in economically developed regions such as Europe and the United States [11][12][13][14][15]. Typhoid fever is transmitted mainly through contaminated food and drinking water [16].…”
Section: Distribution Of Pathogenic Bacteriamentioning
confidence: 99%